The Athens Conservatory Concert Hall by Jan Despo - Tilemachos Andrianopoulos (Joelho)
The Athens Conservatory is the only realized building of the Athens Cultural Center -a ’59 urban design composition by Jan Despo. The upper floor Concert Hall served as the Conservatory’s music venue for 40 years, though it remained in an incomplete, decadent state. Before attempting the restoration, a thorough research of the archived drawings revealed a series of elevations and construction drawings of a visually astonishing composition of acoustic panels for the lateral walls -that was never constructed. The discovery of those original drawings highlights the crucial role of research for a well documented, valid restoration